1996
DOI: 10.1074/jbc.271.46.28912
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase Cα Is a Major Mediator of the Stimulatory Effect of Phorbol Ester on Phospholipase D-mediated Hydrolysis of Phosphatidylethanolamine

Abstract: Stimulation of phospholipase D (PLD)-mediated hydrolysis of phosphatidylcholine (PtdCho) by phorbol 12-myristate 13-acetate (PMA) has been shown to be mediated by the ␣-and ␤I-isoforms of protein kinase C (PKC). To determine the role of various PKC isozymes in the regulation of PLD-mediated phosphatidylethanolamine (PtdEtn) hydrolysis, MCF-7 human breast carcinoma cells overexpressing the ␣-and -isoforms, and R6 rat fibroblasts overexpressing the ␣-, ␤I-, and ⑀-isoforms were used. In the vector control MCF-7 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 33 publications
(29 reference statements)
1
35
0
Order By: Relevance
“…Rat-1 cells express only PKC isoforms ␣, ␦, ⑀, , and but not ␤1 and ␤2, ␥, , or . PKC␣ and ␤1/2 are the only isoforms that have been reported to activate PLD in vitro (Mukherjee et al, 1996;Ohguchi et al, 1996). Therefore, the absence of effect of Gö 6976,, and PKC␣ AS on PLD activity, the lack of effect of PKC␣ depletion on PKC␤1/2 and PKC␦ or PKC⑀ depletion on PKC␣ level, and the inability of PHE to activate classical PKCs rules out PKC␣ involvement in PLD activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rat-1 cells express only PKC isoforms ␣, ␦, ⑀, , and but not ␤1 and ␤2, ␥, , or . PKC␣ and ␤1/2 are the only isoforms that have been reported to activate PLD in vitro (Mukherjee et al, 1996;Ohguchi et al, 1996). Therefore, the absence of effect of Gö 6976,, and PKC␣ AS on PLD activity, the lack of effect of PKC␣ depletion on PKC␤1/2 and PKC␦ or PKC⑀ depletion on PKC␣ level, and the inability of PHE to activate classical PKCs rules out PKC␣ involvement in PLD activation.…”
Section: Discussionmentioning
confidence: 99%
“…Although only classical PKC subtypes have been implicated in PLD activation in vitro (Ohguchi et al, 1996) or in cells overexpressing classical PKC (Mukherjee et al, 1996), there are reports indicating receptor-mediated PLD activation that is independent of PKC (Yang et al, 1998;Muthalif et al, 2000). PLD activation by classical PKCs does not involve a phosphorylation mechanism in vitro (Singer et al, 1996).…”
mentioning
confidence: 99%
“…Indeed, in the early days of TGF-β research, the use of dense, confluent cell cultures was often preferred to better understand the broad capacity of TGF-β to regulate gene expression and/or differentiation. For example, confluent skin, gingival or lung fibroblasts (Chung et al, 1996; Daniels et al, 2004; Mauviel et al, 1994; Wrana et al, 1991), keratinocytes (Kon et al, 1999; Mauviel et al, 1996), chondrocytes (Redini et al, 1991), and/or calvarial bone cells (Wrana et al, 1988), to cite a few, all respond to TGF-β with increased or decreased expression of fibrillar and non-fibrillar collagens (Chung et al, 1996; Kon et al, 1999; Mauviel et al, 1994), fibronectin (Daniels et al, 2004; Ignotz et al, 1989), SPARC (Wrana et al, 1991), laminins (Korang et al, 1995), integrins (Heino and Massagué, 1989), proteoglycans (Redini et al, 1991), metalloproteinases and protease inhibitors such as plasminogen activator inhibitor 1 (PAI-1) or tissue inhibitor of metal-loproteases (Mauviel et al, 1996; Overall et al, 1989). Likewise, early-response genes are efficiently induced by TGF-β in confluent skin fibroblasts and keratinocytes (Mauviel et al, 1993, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…By searching TRANFAC database (http://www.cbrc.jp/research/db/TFSEARCH.html) and other publications (Chung et al, 1996; Kyo et al, 1997; Lee et al, 1987), several putative AP-1/c-Jun binding motifs (Fig 4A) were identified in the 5′ flanking region (−5kb) from the SPLUNC1 transcription start site. To further investigate the role of c-Jun in Pam 3 CSK 4 -mediated SPLUNC1 gene regulation, we determined c-Jun binding to the 5′ flanking DNA region (up to −2.5kb) of SPLUNC1 gene including the sequence of our SPLUNC1 promoter reporter construct (−943/+47 base).…”
Section: Resultsmentioning
confidence: 99%